2021
DOI: 10.5603/cj.a2019.0033
|View full text |Cite
|
Sign up to set email alerts
|

Selected matrix metalloproteinases activity and hypertension-mediated organ damage in relation to uric acid serum level

Abstract: Background: Atherosclerosis is as a systemic inflammatory disease associated with the activation of many mediators, including matrix metalloproteinases (MMPs), and may be amplified by abnormal high serum uric acid (UA) concentration (hyperuricemia, HU). The aim of the study was to determine the relationship between serum UA concentration and activity of MMPs and their correlation with the hypertension-mediated organ damage (HMOD) intensity. Methods: One hundred and nine patients untreated with antihypertensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Higher serum UA concentrations were found to be associated with higher mean arterial pressure and hypertension [39] as well as with an increased risk of type 2 diabetes [40]. A possible positive relation of serum uric acid to MMPs [41,42] as well as negative correlation between SOD and uric acid were documented. It has been found that decreased levels of antioxidants such as SOD in plasma and tissues are associated with increased UA levels in blood circulation [43].…”
Section: Discussionmentioning
confidence: 88%
“…Higher serum UA concentrations were found to be associated with higher mean arterial pressure and hypertension [39] as well as with an increased risk of type 2 diabetes [40]. A possible positive relation of serum uric acid to MMPs [41,42] as well as negative correlation between SOD and uric acid were documented. It has been found that decreased levels of antioxidants such as SOD in plasma and tissues are associated with increased UA levels in blood circulation [43].…”
Section: Discussionmentioning
confidence: 88%
“…In our opinion, patients with potentially reversible cardiovascular changes are most likely to receive the greatest benefits from intensive ULT used in parallel with the modification of other cardiovascular risk factors as part of primary prevention of ischemic heart disease. We have previously shown that a higher UA concentration via higher serum matrix metalloproteinase (MMP) 3 enhances selected HMOD, especially carotid IMT in patients with AH [37]. Extracellular MMPs are part of inflammation leading to the degradation of collagen, vessel remodeling and atherosclerotic plaque rupture [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…In our opinion patients with potentially reversible cardiovascular changes are most likely to receive the greatest bene ts from intensive ULT used in parallel with the modi cation of other cardiovascular risk factors as part of primary prevention of ischemic heart disease. We have previously shown that a higher UA concentration via higher serum matrix metalloproteinase (MMP) 3 enhances selected HMOD, especially carotid IMT in patients with AH [37]. Extracellular MMPs are part of in ammation leading to the degradation of collagen, vessel remodelling and atherosclerotic plaque rupture [38,39].…”
Section: Discussionmentioning
confidence: 99%